Sleep and Quality of Life in Clinical Medicine
DOI: 10.1007/978-1-60327-343-5_27
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Quality of Life in Depression

Abstract: Summary Major depression is a common disorder; nearly 10% of the population suffers from a depressive illness in any given year. There is a strong association between sleep disturbances and depression. The most common sleep disturbance associated with major depressive disorder is insomnia. The relationship between insomnia and depression is bidirectional in that insomnia is one of the symptoms of depression and chronic insomnia can be a risk factor for depression. Depression causes changes in sleep patterns an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 109 publications
2
2
0
Order By: Relevance
“…Depression not only caused the changes in sleep patterns and sleep quality, but individuals having depressive symptoms also had poorer quality of life than the general population. 24 Our study was consistent with this finding. In a previous study to subjectively evaluating quality of life, physical activity enhanced quality of life, which was generated from social, physical, cognitive, emotional and spiritual well-being components.…”
Section: Discussionsupporting
confidence: 92%
“…Depression not only caused the changes in sleep patterns and sleep quality, but individuals having depressive symptoms also had poorer quality of life than the general population. 24 Our study was consistent with this finding. In a previous study to subjectively evaluating quality of life, physical activity enhanced quality of life, which was generated from social, physical, cognitive, emotional and spiritual well-being components.…”
Section: Discussionsupporting
confidence: 92%
“…Theses 3% students are at suicidal risk. This finding is relevant to the findings of Caliyurt (2008).…”
Section: Resultssupporting
confidence: 66%
“…People with severe depression may plan or attempt suicide. Research showed that up to 15% of those who are clinically depressed die by suicide (Caliyurt 2008) Somatization is also a common mental health problem. It is a process in which psychological distress is expressed in multiple physical symptoms that have no discernible medical cause (Smith 1990).…”
Section: Introductionmentioning
confidence: 99%
“…These included multiple sclerosis (de Vries, 2008); Parkinson's disease (Whitehead et al, 2008); Huntington's disorder, Shy-Drager syndrome, polysensory neuritis, amyotrophic lateral sclerosis, spinal muscular atrophy (Dauvilliers, 2007); brain and spinal cord injuries (Piper, 2008); cerebral palsy (Kotagal et al, 1994); stroke, end-stage cardiac disease (Roth, 2009;Skobel et al, 2008); COPD (Herdegen, 2006); diabetes (Skomro, 2008); chronic renal disease (Patel et al, 2008); and cancer (Paltiel & Greenwald, 2008). Illnesses associated with poor sleep also included a current diagnosis of depression (Caliyurt, 2008), which was measured by current treatment with antidepressants.…”
Section: Methodsmentioning
confidence: 99%